Diversity of plasmids in Staphylococcus saprophyticus isolated from urinary tract infections in women. - Cristino, J. A. (Cambridge University Press, 1989)
A group of 150 Staphylococcus saprophyticus strains isolated from urinary tract infections in women were included in this study. Antimicrobial susceptibility tests showed that these isolates were sensitive to most antimicrobial agents. All strains were sensitive to penicillin, cephalothin, gentamicin, kanamycin, trimethoprim and nitrofurantoin. Resistance to tetracycline was present in 10.6% of the strains, to chloramphenicol in 4%, to erythromycin in 1.3% and to streptomycin in 1.3%. All strains were resistant to cadmium chloride as well as to novobiocin and nalidixic acid. Plasmid analysis showed that 82% of the strains harboured plasmids, some of them with complex plasmid profiles. Most plasmids were considered to be cryptic, although antibiotic resistance plasmids were identified in 18 isolates. Tetracycline resistance was encoded by a plasmid of c. 2.8 MDa, chloramphenicol resistance by a plasmid of c. 2.9 MDa and erythromycin resistance by a plasmid of c. 1.6 MDa. Streptomycin resistance could not be linked to the presence of any specific plasmid. Plasmid profiling seemed to be a good method for differentiating among S. saprophyticus strains.